2022
DOI: 10.3389/fpubh.2021.817882
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Between Increase of Axial Length and Height Growth in Chinese School-Age Children

Abstract: PurposeTo identify the relationship between the increase in axial length (AL) and height in school-age children and explore the influence of refractive status on such a relationship.MethodsIn this 5-year cohort study, 414 Chinese children (237 boys) aged 6–9 years (mean 7.12) underwent measurements annually. AL was measured using the Lenstar; height with the children standing, without shoes; and refraction using subjective refraction without cycloplegia. Participants were divided according to the refractive st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 52 publications
0
8
1
Order By: Relevance
“…The AL and AL/CR ratio of boys were 0.43 mm and 0.03 higher than that of girls, respectively. These differences may be due to the harmony between eye growth and the body ( 34 ). Saw et al analyzed the height and AL of 1,449 children aged 7–9 years and showed that taller children have a longer AL ( 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…The AL and AL/CR ratio of boys were 0.43 mm and 0.03 higher than that of girls, respectively. These differences may be due to the harmony between eye growth and the body ( 34 ). Saw et al analyzed the height and AL of 1,449 children aged 7–9 years and showed that taller children have a longer AL ( 35 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have shown controversial results on these associations and have mainly been studied in China. [99][100][101][102][103][104][105][106][107] Time spent asleep, outdoors and on near work did not differ between the two groups, even after accounting for age. However, multiple linear regression models showed that M is predicted by age and time spent outdoors, and AXL by age, time spent outdoors and time asleep.…”
Section: Discussionmentioning
confidence: 86%
“…No effect of weight or height was observed in M, AXL or AXL/CR after accounting for age. Previous studies have shown controversial results on these associations and have mainly been studied in China 99–107 . Time spent asleep, outdoors and on near work did not differ between the two groups, even after accounting for age.…”
Section: Discussionmentioning
confidence: 87%
“…The AL plays a vital role in refraction, but a long AL does not necessarily mean more severe myopia. Emmetropia is a balance between AL, corneal power and lens power ( 22 ). In patients with emmetropes or low myopia, the function of the cornea seems to compensate for the possible myopic effects of slight increases in AL.…”
Section: Discussionmentioning
confidence: 99%